Conocimientos, actitudes y prácticas sobre uso de antibióticos y resistencia antimicrobiana en usuarios de la farmacia Institucional DIREMID, Iquitos 2025 - Gallardo Vásquez, Mónica Lucero (2025)
Objective: To determine the levels of knowledge, attitudes, and practices regarding the use of antibiotics and antimicrobial resistance among users of the DIREMID institutional pharmacy. Methodology: Descriptive, observational, and cross-sectional study. Results: A total of 252 participants were surveyed. The sex distribution was balanced (50.4% men and 49.6% women). The predominant group was aged 26–35 years (31%), single (50.6%), residents of the Iquitos district (50.8%), with technical education (36.7%), and employed as dependent workers (40.8%). Most participants showed regular levels of knowledge (54.8%), attitudes (54.8%), and practices (52.4%). Overall, 50.6% believed antibiotics are also effective against viral infections, 53.2% reported discontinuing treatment upon perceiving clinical improvement, only 37.7% had previously heard the term “antimicrobial resistance,” and just 16.5% always acquired antibiotics with a medical prescription. Positive correlations were found between knowledge, attitudes, and practices (p < 0.001). Higher educational attainment was significantly associated with better levels of knowledge (p < 0.001), attitudes (p = 0.003), and practices (p = 0.029). In multivariate analysis, primary education was associated with a lower likelihood of achieving adequate knowledge (OR = 0.007; p < 0.001) and attitudes (OR = 0.039; p = 0.009). No significant predictors were identified for practices. Conclusions: Most participants demonstrated regular levels of knowledge, attitudes, and practices, highlighting the need to implement educational strategies that promote the rational use of antibiotics and reduce antimicrobial resistance.